New period of social development and taxing problems (Journal of actual problems of jurisprudence, 2018)
Present article raises the question of introduction of new taxation method in accordance with social development. For this there are proposed ways of transition to easy and comfortable taxation methods for the taxpayer, tax administration and for the government, in addition examples show that for the achievement of better results all parties should closely follow the development process of public life and consequently coherent action will bring to the better imposition of tax, mutual trust and confidence will grow and relying on the size and function of tax particular spheres will be revived, new relationship will appear and the most important all these action will become a measuring instrument of government’s performance on resolving the problems appearing in the particular period.Key words: income of the taxpayer, interest rate, mutual trust between tax administration and taxpayer, defrauding of income, penalty for defrauding of income, tax rate on income of the taxpayer, government’s function on determination of tax rate on income of the taxpayer.